Supplementary Table S4 from Blood-Based Diagnosis and Risk Stratification of Patients with Pancreatic Intraductal Papillary Mucinous Neoplasm (IPMN) - Chaoyang Zhang (15051876) (2025)
Normalized signal intensity variations obtained on the antibody microarray.